2019
DOI: 10.1080/17461391.2018.1563633
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality in young adults with intellectual disability involved in adapted competitive football

Abstract: The objective of this study was to analyse bone quality parameters of football players with intellectual disability (ID) participating in adapted competitive football. Sixty-seven male football players with ID were studied: 22 with Down syndrome (DS) and 45 without DS. The average age was 26 years (range: 16 ̶ 50 years). A group of 25 age-matched sedentary individuals with ID (11 DS and 14 non-DS) and another group of 20 healthy participants of the same age group not involved in competitive football were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Based on cross‐sectional data of SOS among Malaysian men (mean ( SD ) = 1,520.2 (30.4) m/s) (Chin et al, ), recruiting 37 participants would be sufficient to detect a true difference of 20 m/s (Lizondo, Caplliure‐Llopis, Escriva, De La Rubia, & Barrios, ) (80% power and 5% probability of type I error). After allowing for a 20% of dropout, a total of 44 participants from each group were required.…”
Section: Methodsmentioning
confidence: 99%
“…Based on cross‐sectional data of SOS among Malaysian men (mean ( SD ) = 1,520.2 (30.4) m/s) (Chin et al, ), recruiting 37 participants would be sufficient to detect a true difference of 20 m/s (Lizondo, Caplliure‐Llopis, Escriva, De La Rubia, & Barrios, ) (80% power and 5% probability of type I error). After allowing for a 20% of dropout, a total of 44 participants from each group were required.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Lizondo et al, analyzed and compared bone quality parameters of different ID groups and people without ID. Based on the results, authors suggested that physical activity improves bone mass in ID individuals, therefore it should be recommended for preventive care (Lizondo et al, 2019). In a different sport, on a periodized swimming training program in individuals with Down's syndrome, improvements were found on swimming speed and performance times in sprint distances.…”
Section: Sport Participation and Its Effect On Physical State Of People With Disabilitiesmentioning
confidence: 99%
“…Interventions with both aerobic and resistance training has shown that the participants experienced the benefits from both these modalities, within 10-20 weeks (Calders et al, 2011; Elmahgoub et al, 2011; Oviedo, Guerra-Balic, Baynard, & Javierre, 2014). PA for individuals with ID seem to induce reductions in body weight and fat mass (Elmahgoub et al, 2011; Son, Jeon, & Kim, 2016), and improved bone health (González-Agüero et al, 2012; Lizondo, Caplliure-Llopis, Escrivá, De La Rubia, & Barrios, 2019), but the results are equivocal within these areas, and more research is warranted. Improvements in the above-mentioned domains have a positive influence on general health.…”
Section: Introductionmentioning
confidence: 99%